Tracking the Subsolar Bow Shock and Magnetopause. Issue 9 (26th September 2022) - Sibeck, D. G.; Silveira, M. V. D.; Collier, M. R.
Abstract: Global magnetohydrodynamic models predict that plasma velocities vary almost linearly from 0 km s −1 at the nose of the stationary magnetopause on the stagnation streamline to a limiting value of 0.25 V SW for high solar wind Alfvénic Mach numbers at the nose of the bow shock, where V SW is the solar wind velocity. This paper presents a proof‐of‐concept study showing how two‐point measurements of the plasma velocity in the subsolar magnetosheath can be used to determine gradients in the plasma velocity and consequently the steady‐state or slowly moving locations of both the nose of the magnetopause and the nose of the bow shock. The results may be of use to those binning magnetosheath observations to develop empirical models, those testing models for magnetopause erosion or deposition in response to magnetic reconnection, and those determining the stand‐off distance of the bow shock as a function of solar wind conditions. Plain Language Summary: We employ dual‐spacecraft observations to determine the radial gradient in plasma velocity through the subsolar magnetosheath. Relying upon results from global magnetohydrodynamic simulations indicating that this gradient is linear, we use it to determine the locations of the bow shock and magnetopause positions. Key Points: Plasma velocities vary almost linearly along the stagnation streamline from the nose of the magnetopause to the nose of the bow shock Magnetohydrodynamic theory and models predict magnetosheath plasma velocities at the noses of the bow shock and magnetopause Radial gradients in the plasma velocity define the locations of the stationary or slow‐moving subsolar magnetopause and bow shock